1985
DOI: 10.1111/j.1574-6968.1985.tb01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellulolytic activity of Actinomycetes isolated from termites (Termitidae) gut

Abstract: Cellulolytic actinomycetes were isolated from the hindgut of four different termites: Macrotermes, Armitermes, Odontotermes and Microcerotermes spp. The isolated actinomycetes (Streptomyces sp. and Micromonospora sp.) were grown on cellulosic substrates and their extracellular cellulase (Cl, Cx and cellobiase) activity evaluated; using filter paper as a substrate for Cl, carboxymethylcellulose (CMC) for Cx and d‐cellobiose for cellobiase, all strains were shown to degrade soluble and insoluble cellulose; optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“…This result suggests that Actinobacteria transferred to the wheat bran when the house fly larvae were feeding. Actinobacteria associated with termites facilitate nutrient acquisition from diverse polysaccharides, including cellulose (Pasti and Belli 1985; Watanabe et al 2003) and hemicelluloses (Schäfer et al 1996), and Actinobacteria may similarly facilitate the utilization of polysaccharides in wheat bran by house flies. Arabinoxylans and β-glucans are polysaccharides in the cell wall of wheat bran and have a potential role in lowering the risk of type II diabetes, colorectal cancer and cardiovascular and diverticular diseases (Poutanen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that Actinobacteria transferred to the wheat bran when the house fly larvae were feeding. Actinobacteria associated with termites facilitate nutrient acquisition from diverse polysaccharides, including cellulose (Pasti and Belli 1985; Watanabe et al 2003) and hemicelluloses (Schäfer et al 1996), and Actinobacteria may similarly facilitate the utilization of polysaccharides in wheat bran by house flies. Arabinoxylans and β-glucans are polysaccharides in the cell wall of wheat bran and have a potential role in lowering the risk of type II diabetes, colorectal cancer and cardiovascular and diverticular diseases (Poutanen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These microbes possess diverse bioactive functions to biosynthesize several applicable metabolites such as enzymes (3, 19, 26, 27, 29, 32) and antimicrobial substances (20, 21). Few studies have evaluated the antimicrobial function of cultivable actinobacteria isolated from termite-related sources especially in the termite gut (20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined the microbial biota within the termite gut, and actinobacteria were identified as one of the dominant bacteria in this symbiotic lifestyle (3, 6, 20, 21, 26, 27). These symbiotic actinobacteria provide assisting functions for termites, such as nutrient cycling and exchange, and also protect termites from invading pathogens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). All other known insect-associated actinomycetes (gut associates of Culex mosquitos, [57], and of termites, [58] belong to the Streptomycetinae, a subfamily to which none of our sequences belongs. In conclusion, from the information currently present we cannot say what effect the isolated actinomycete strains may have on A. octospinosus.…”
Section: Discussionmentioning
confidence: 99%